Effect of Borax On Sintering Kinetics, Microstructure and Mechanical Properties of Porous Glass-Ceramics From Coal Fly Ash by Direct Overfiring - Zeng, Li; Sun, Hongjuan; Peng, Tongjiang (Frontiers in Chemistry, 2022)
The direct sintering process of coal fly ash for the preparation of glass-ceramics is the liquid-phase sintering process from non-densification to densification. When the temperature exceeds the densification temperature point, the porosity of glass-ceramics on the contrary increases and the pore diameter increases. This provides a basis for direct overfiring of porous glass-ceramics. Adding borax to coal fly ash can reduce the temperature of liquid phase formation, reducing the preparing temperature of porous glass-ceramics by overfiring, achieving the purpose of energy saving. The effects of borax on the structure, properties and sintering kinetics of porous glass-ceramics prepared from coal fly ash by overfiring were investigated. It is found that the introduction of B-O bond can change the network structure of non-crystalline vitreous in coal fly ash, reduce its melting temperature, promote the formation of liquid phase, and thus increase the porosity of porous glass-ceramics. This paper provides a certain experimental basis for the preparation of porous glass-ceramics by direct overfiring of coal fly ash at low temperature without adding pore-forming agent, and provides a new possibility for the high-value resource utilization of coal fly ash.